Gelation of beta-lactoglobulin in the presence of propylene glycol alginate: kinetics and gel properties - Baeza, Rosa Isabel (2003)
The role of the non-gelling polysaccharide, propyleneglycol alginate (PGA), on the dynamics of gelation and gel properties of β-lactoglobulin (β-lg) under conditions where the protein alone does not gel (6%) was analyzed. To this end, the kinetics of gelation, aggregation and denaturation of β-lg in the mixed systems (pH 7) were studied at different temperatures (64–88 °C). The presence of PGA increased thermal stability of β-lg. The rate of β-lg denaturation was decreased and the onset and peak denaturation temperatures increased by 2.2–2.4 °C. PGA promoted the formation of larger aggregates that continued to grow in time. An average aggregate diameter of approximately 300 nm is reached at the gel point in the mixed β-lg+PGA systems, irrespective of the heating temperature. Comparing the activation energies for the aggregation (193 kJ/mol), denaturation (422 kJ/mol) and formation of the primary gel structure (1/tgel) (256 kJ/mol) processes in the mixed protein–polysaccharide system, it can be concluded that the rate determining step in the formation of the primary gel structure would be the aggregation of protein. Ea values for the processes after the gel point (solid phase gelation) suggest a diffusion limited process because of the high viscosity of the solid gelling matrix. The characteristics of the mixed β-lg+PGA gels in terms of rheological and textural parameters, water loss and microstructure were studied as a function of heating temperature and time. The extent of aggregation and the type of interactions involved, prior to denaturation seem to be very important in determining the gel structure and its properties.